How does teacher bias influence students?: An introduction to the special issue on teachers' implicit attitudes, instructional practices, and student outcomes. (April 2022) - DeCuir-Gunby, Jessica T.; Bindra, Vandna Gill
Abstract: Implicit bias, unconscious beliefs based upon stereotypes and prejudices, has emerged as a useful way to understand and explain issues of discrimination, particularly involving race. The influence of implicit bias has been explored in various academic disciplines and numerous contexts, including education. Despite the burgeoning research literature, there is limited research on the role implicit bias plays within the classroom. The goal of this special issue is to broaden and challenge the current thinking on teacher implicit bias and attitudes as well as their influence on students. Highlights: Implicit biases are unconscious stereotypes that influences perceptions. Teachers' explicit beliefs influence students' learning and achievement. Racial/ethnic students are often influenced by teachers' implicit biases.